First principle calculations and mechanical properties of the intermetallic compounds in a laser welded steel/aluminum joint. (February 2020) - Li, Yulong; Liu, Yanru; Yang, Jin
Highlights: Properties of Fe-Al IMCs were systematically calculated using the first-principle. Lattice constants, mechanical properties and electronic structures were obtained. Fe-rich phases are superior to Al-rich phases on the mechanical properties. 316L stainless steel and 6061 aluminum were laser welded using T-joint. The calculated results were verified with the experiments. Abstract: To analyze the IMC (Intermetallic Compound) properties and their effects on steel/aluminum welding, the equilibrium lattice constants, mechanical properties and electronic structures of the intermetallic compounds Fe3 Al, FeAl, Fe2 Al5, FeAl2, FeAl3 and Fe4 Al13 were systematically calculated using the first-principle methods. The results show that the calculated elastic constants of the IMCs satisfy the mechanical stability conditions. Fe3 Al and FeAl2 exhibit plastic characteristics; FeAl, Fe2 Al5, FeAl3, and Fe4 Al13 exhibit brittle characteristics; Fe-Al binary compounds have typical metallic properties; and the 3d bands of Fe contribute most significantly to the total density of states. In the vicinity of the Fermi level, the 3d bands of Fe contribute together with the bands of Al; the Fe-Al binary compounds have weak ionicity, relatively high hardness and high melting points; additionally, the effects of Fe-rich phases on the mechanical properties of the joints are superior compared to Al-rich phases. To verify the first principle calculations, T-joint laser welding experiments were conducted on 316L stainless steel and 6061 aluminum alloy sheets. The microstructure, reaction phases, fracture morphologies and mechanical properties of the welded joint were analyzed by optical microscopy, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) and nanoindentation. According to the XRD and EDS analysis, Fe3 Al, FeAl, Fe2 Al5, FeAl2, FeAl3 and Fe4 Al13 were formed; their properties and effects on the joint of these phases are consistent with the calculated results.